2019
DOI: 10.1002/cjp2.145
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of PAXgene® tissue fixation for the histopathological and molecular study of lung cancer

Abstract: Whilst adequate for most existing pathological tests, formalin is generally considered a poor DNA preservative and use of alternative fixatives may prove advantageous for molecular testing of tumour material; an increasingly common approach to identify targetable driver mutations in lung cancer patients. We collected paired PAXgene® tissue‐fixed and formalin‐fixed samples of block‐sized tumour and lung parenchyma, Temno‐needle core tumour biopsies and fine needle tumour aspirates (FNAs) from non‐small cell lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…However, other QC metrics were not evaluated in that study. Southwood et al, applying the Qiagen sequencing platform on PFPE lung tissues, reported superior NGS performance, both in terms of QC metrics and for variant calling with higher unique molecular identifier (UMI) reads and deeper mean depth of coverage than those of FFPE tissues [ 9 ]. We did not observe PFPE tissues exhibiting more mapped reads nor deeper mean depth of coverage using the Ion Torrent platform.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other QC metrics were not evaluated in that study. Southwood et al, applying the Qiagen sequencing platform on PFPE lung tissues, reported superior NGS performance, both in terms of QC metrics and for variant calling with higher unique molecular identifier (UMI) reads and deeper mean depth of coverage than those of FFPE tissues [ 9 ]. We did not observe PFPE tissues exhibiting more mapped reads nor deeper mean depth of coverage using the Ion Torrent platform.…”
Section: Discussionmentioning
confidence: 99%
“…A recently developed methanol and acetic acid-based fixative, PAXgene (PAXgene Tissue Fix Container, Preanalytix GmbH, Hombrechtikon, Switzerland), works via a non-crosslinking mechanism. Studies involving multiple types of cancer have demonstrated that PAXgene-fixed, paraffin-embedded (PFPE) tissue yields adequate histomorphology in the majority of cases (i.e., comparable to FFPE, far better than frozen tissue) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. These studies also suggested PFPE is associated with improved DNA and RNA yield and quality compared to FFPE [ 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, prior studies have shown PAXgene fixation is superior in preserving RNA integrity, particularly in low-yield samples for molecular experiments [3,5,25]. It also was reported that the PAXgene-fixed RNA has better RT-PCR efficiency than NBF fixation and was comparable to snap-frozen samples, irrespective of the length of the mRNA, in a wide variety of cancerous tissues, including squamous cell carcinoma [5,25,26]. Further in-depth comparative studies are warranted in oral tissue to understand the effect of PAXgene fixation on RNA integrity and downstream analysis such as RT-PCR and RNA sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Especially during the natural history of longlasting cancers, the possible contribution of core-needles as repeat biopsies is debated. Traditionally, processed formalin-fixed paraffin-embedded (FFPE) samples have been compared to paired PAXgene ® tissue fixed paraffinembedded (PFPE) tissues, which might be superior for DNA and RNA integrity, particularly in low-yield samples (15). Cytology and micro-histological approaches might work in a complementary fashion (16), however, when neoplastic sites are not accessible or clinicians have not the possibility to apply an interventional procedure with the requested advantage, the recourse to liquid biopsy is completely justified.…”
Section: Biological Techniquesmentioning
confidence: 99%